Tinjauan Yuridis Terhadap Eksploitasi Anak (Studi Komparasi Eksploitasi Anak di Jalanan dan Konten Kreator) - Iqhbal Putra Pratama; Iwan Iwan (Journal of Law, Society, and Islamic Civilization, 2024)
Exploitation is one of the problems based on poverty, the situation results in a change in perspective so that it justifies any means to continue living. Children are often victims of exploitation where parents/guardians order children to busk, beg, sell on the side of the road and others. Along with the times with the sophistication of technology, these actions have also developed, with new packaging that is neatly covered in such a way that exploitation is carried out by making children the object of content creators. Children are ordered to live on social media platforms such as shopee live whose scope is used to sell and gain profit. the prosecution carried out against child exploitation on social media is still of little concern, this states that there is a legal disparity where child exploitation on the streets is more firmly dealt with. The purpose of the research is to review from a juridical point of view with regulations relating to child exploitation while emphasizing that children who are used as objects of content creators are also a form of child exploitation, both of which have the same essence, namely involving children for profit, only the container makes the difference. This research uses normative juridical methods (legal research). The results of this study confirm that based on Law No.35 of 2014 concerning child protection and Law No.13 of 2003 concerning labor that people who make children as objects of content creators are included in child exploitation because they take advantage of children and sacrifice children's rights. The government and law enforcement officials and related agencies should pay more attention to this and take action in accordance with the relevant laws.